2022
DOI: 10.3389/fphar.2022.940628
|View full text |Cite
|
Sign up to set email alerts
|

Role of tannic acid against SARS-cov-2 cell entry by targeting the interface region between S-protein-RBD and human ACE2

Abstract: Coronavirus disease 2019 (COVID-19) was caused by a new coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 utilizes human angiotensin converting enzyme 2 (hACE2) as the cellular receptor of its spike glycoprotein (SP) to gain entry into cells. Consequently, we focused on the potential of repurposing clinically available drugs to block the binding of SARS-CoV-2 to hACE2 by utilizing a novel artificial-intelligence drug screening approach. Based on the structure of S-RBD and hA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…In addition, tannic acid has shown potent inhibition of main protease (Mpro)/3CLpro and TMPRSS2, which are essential proteins for the propagation of SARS-CoV-2 [69,70]. In particular, it was confirmed that tannic acid prevented pseudotyped SARS-CoV-2 entrance by preventing S-RBD from attaching to ACE2 [71,72]. Notably, orally administered tannic acid isomers have exhibited effectiveness against SARS-CoV-2 variants such as Delta and Omicron [73].…”
Section: Antiviral Activities Of Compounds Against the Pseudotyped Vi...mentioning
confidence: 96%
“…In addition, tannic acid has shown potent inhibition of main protease (Mpro)/3CLpro and TMPRSS2, which are essential proteins for the propagation of SARS-CoV-2 [69,70]. In particular, it was confirmed that tannic acid prevented pseudotyped SARS-CoV-2 entrance by preventing S-RBD from attaching to ACE2 [71,72]. Notably, orally administered tannic acid isomers have exhibited effectiveness against SARS-CoV-2 variants such as Delta and Omicron [73].…”
Section: Antiviral Activities Of Compounds Against the Pseudotyped Vi...mentioning
confidence: 96%